Research on Grid Scroll Chaotic Extended Sequence Algorithm and Its Circuit Implementation for F-OFDM System. (28th November 2019) - Ma, Yingjie; Li, Ya; Zhao, Geng; Zeng, Ping; Yang, Yatao
Abstract : High peak-to-average power ratio (PAPR), a main problem of 5G Filtered-Orthogonal Frequency Division Multiplexing (F-OFDM) system, seriously affects the system's transmission efficiency. Aiming at the shortcomings of the traditional selective mapping (SLM) algorithm, the grid scroll chaotic extended sequence (GSCES) algorithm is proposed to solve the high PAPR problem. The proposed grid multiscroll chaotic maps are used as random phase sequence vectors instead of the traditional pseudo random sequence, which provide a large number of random sequences with good correlation characteristics, random characteristics, and high security. The proposed random phase sequence vectors can meet the needs of 5G mass connections. The original input signals are divided into real part and imaginary part, which are, respectively, dot produced with the proposed grid multiscroll chaotic maps. The numerical simulation results show that the proposed GSCES algorithm effectively increases the number of candidate sequences, reduces the PAPR values, and improves the transmission efficiency and security. Moreover, the hardware experimental results produce at 2 × 2 × 2-grid multiscroll chaotic attractor, which further proves the physical realization of the proposed system. The proposed schemes have a broad application prospect in 5G multicarrier modulation technology.